Peran Etnomatematika dalam Pendidikan Matematika di Tingkat Sekolah Dasar - Azamul Fadhly Noor Muhammad; Gunawan Gunawan (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Ethnomathematics is a mathematical concept contained in a culture. The presence of mathematics with cultural nuances will make a major contribution to mathematics learning, especially at the elementary school level. The purpose of this study is to identify and describe the role of Ethnomathematics in mathematics learning, especially in the realm of elementary school. This research is descriptive research with an inventory approach. In the implementation of this research, the steps are as follows: 1) Topic selection; 2) Exploring information; 3) Determining the focus of research; 4) Collecting data; 5) Preparing data presentation; and 6) Reporting preparation. The results of this study show that learning mathematics in Ethnomathematics at the elementary school level emphasizes the content of the material or curriculum and direct practice in applying ethnomathematics learned by students in the classroom. Ethnomathematics learning in elementary schools can be defined as special ways carried out by teachers in carrying out mathematics learning process activities in elementary schools related to culture, either in the form of forms or habits that are often encountered by students.